THE EFFECT OF RECORDED (VIDEOTAPED) MINI-DRAMA TOWARD STUDENTS’ SPEAKING ABILITY - Melviola Fitri; Putri Yulia Sari; Yummi Meirafoni (Universitas Negeri Padang, 2016)
The aim of this study is to determine the effects of using the technique named recorded (videotaped) mini-drama toward students’ speaking ability. Students’ speaking ability can be seen from the five aspects of a rubric used, which are pronunciation, fluency, comprehension, grammar, and vocabulary. Researchers conducted observations at SMA N 2 Padang in order to see the techniques applied by the teachers in the classroom that affect to students’ speaking ability. Researchers found several weaknesses of the teaching techniques which are implemented in schools. Those techniques influence students' speaking ability. To overcome the problems, the researchers applied a technique called recorded (videotaped) mini-drama. In this technique, students performed a mini-drama and the researcher record the performance. In the next meeting, the recording was showed in front of the class and then the researchers discussed it with the students by considering the five aspects of the rubric. After the technique applied in the classroom, the researchers held a posttest to see the effect of the technique. Posttest assessed by two English teachers from SMA N 2 Padang with reference to the five aspects previously mentioned. Based on this research, it was found that the technique recorded (videotaped) mini-drama gives a significant effect on students' speaking ability.